Analisis Kredit Bermasalah pada Koperasi Simpan Pinjam di Desa Waiheru (Studi Kasus pada Koperasi Serba Usaha Dwi Eka Jaya) - Warbanaran, Imelda Dina; Kainama, Maryoni Stevanny; Tomasoa, Theodora Florence (Universitas Pattimura, 2024)
Savings and loan cooperatives play an important role in supporting community economies, but often face challenges related to non-performing loans that can impact the financial health of the cooperative. This study aims to identify the factors causing non-performing loans at Dwi Eka Jaya Multi-Business Cooperative in Waiheru Village. A case study with a descriptive qualitative approach was employed, utilizing observation, interviews, and documentation with 13 respondents experiencing problematic loans. The results reveal six main factors: misuse of loan funds, poor character, crop failure, business constraints, misfortune, escape, and additional borrowing from other institutions without increased income. The findings highlight the necessity for thorough debtor assessments and strengthened internal supervision systems to minimize credit risk. These insights provide a deeper understanding of risk dynamics in local cooperatives. The implications suggest the need for credit analysis training, member assistance, and strengthened creditworthiness assessment procedures to support cooperative sustainability.